Epidemiological study of human brucellosis among febrile patients in Erbil-Kurdistan region, Iraq - Dhary Alewy Almashhadany; Zean Fetehallah Zefenkey; Mohammed Naji Ahmed Odhah (Journal of Infection in Developing Countries)
Introduction: Human brucellosis is one of the most common zoonosis infections, with an important impact on the health and economy worldwide. This study aimed to update and provide epidemiological information on this infection and evaluate Rose Bengal Test, which is used as an essential diagnostic test for brucellosis in Erbil.